ANALYSIS AND EVALUATION OF THE PLANNING PROCESS IN A TRANSPORT COMPANY - Zbigniew ŁUKASIK; Aldona KUŚMIŃSKA-FIJAŁKOWSKA; Sylwia OLSZAŃSKA; Mateusz ROMAN (Scientific Journal of Silesian University of Technology. Series Transport)
Today, route planning requires freight forwarders to make a conscious effort to identify unloading points such that the transport process is both cost- and time-efficient. At the same time, operational parameters that help to determine the validity of the chosen route must also be considered. This article aims to present the key metrics and ways of attaining them to provide a reliable determination of a transport company’s performance. Based on a selected transport company, the authors collected data on the transport routes implemented in 2020. Interpretation and analysis of the extracted information of the concerned sections were carried out and followed by alternatives. We present in this article the results of research concerning the exploitation parameters of the vehicle set. The evaluation of a given route section was indicated using selected indicators adapted to the specificity of the enterprise. The results are aimed at locating the components that have a destructive impact on the entire process. The proposed solutions serve to introduce factors that will pave way for improving the services provided. An in-depth analysis of all sections and key parameters was performed. Because of the conducted studies, abnormal parameters were identified, efficient sections were distinguished and new routes were developed in the case of previous routes that were not highly efficient and which had a possible alternative corridor. The obtained results of the research can comprise, for logistics managers, vital elements in the transport process, to which attention should be given in the course of overseeing these processes.